2007
DOI: 10.1002/prot.21733
|View full text |Cite
|
Sign up to set email alerts
|

Information and discrimination in pairwise contact potentials

Abstract: We examine the information-theoretic characteristics of statistical potentials that describe pairwise long-range contacts between amino acid residues in proteins. In our work, we seek to map out an efficient information-based strategy to detect and optimally utilize the structural information latent in empirical data, to make contact potentials, and other statistically derived folding potentials, more effective tools in protein structure prediction. Foremost, we establish fundamental connections between basic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(53 citation statements)
references
References 35 publications
3
50
0
Order By: Relevance
“…In addition, mutual information proved to be successful for the identification of class-specific molecular descriptors [37]. Information theory has been applied for fold recognition and for the identification of correct protein models [38][39][40][41].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, mutual information proved to be successful for the identification of class-specific molecular descriptors [37]. Information theory has been applied for fold recognition and for the identification of correct protein models [38][39][40][41].…”
Section: Discussionmentioning
confidence: 99%
“…The conversion of the probability into an energy function is normally done employing Boltzmann's law 3 . Theory of conditional probabilities 5,6 , linear and quadratic programming 7 and information theory 8 have been invoked to justify the approach. The simplest observable 1,2 that one can use to characterize a structure is the presence of a contact between two specific residues.…”
mentioning
confidence: 99%
“…In this work, we revisit the contact reference state problem using information-theoretic tools we have developed in previous work. We have found that a key determinant of the correct discrimination of native folds amidst an ensemble of incorrect or “decoy” conformations is the total divergence, an information-theoretic entity that quantifies the distance between the score of the correct structure and the mean score of the decoys 8. Here, we demonstrate how the definition of “expected” probability affects the total divergence of contact potentials, and evaluate the impact of the definitions on their effectiveness in actual threading.…”
Section: Introductionmentioning
confidence: 86%